2016
DOI: 10.1002/jbm.a.35705
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of articular cartilage using adipose stem cells

Abstract: Articular cartilage (AC) has limited potential for self-regeneration and damage to AC eventually leads to the development and progression of osteoarthritis (OA). Cell implantation strategies have emerged as a new treatment modality to regenerate AC. Adipose stem cells/adipose-derived stromal cells (ASCs) have gained attention due to their abundance, excellent proliferative potential, and minimal morbidity during harvest. These advantages lower the cost of cell therapy by circumventing time-consuming procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 106 publications
(122 reference statements)
0
27
0
Order By: Relevance
“…The limited potential of articular cartilage for self-regeneration has been attributed to the fact that it is difficult for cells to access the injured site due to the inability of adjacent articular chondrocytes to migrate and produce matrix 55. In our study, SMSC-Exos promoted chondrocyte proliferation and migration, which are inhibited in OA 56.…”
Section: Discussionmentioning
confidence: 55%
“…The limited potential of articular cartilage for self-regeneration has been attributed to the fact that it is difficult for cells to access the injured site due to the inability of adjacent articular chondrocytes to migrate and produce matrix 55. In our study, SMSC-Exos promoted chondrocyte proliferation and migration, which are inhibited in OA 56.…”
Section: Discussionmentioning
confidence: 55%
“…In terms of future direction of ASC therapy, with its discovery nearly 16 years ago, research in ASC application has made significant progress to provide for a promising stem cell therapy tool [95] and interest continues to increase. Regenerative applications of ASC are not limited to bone; ASC have been applied to cartilage repair [97] , cardiovascular regeneration [98] , and even hair [99] among other tissue types. With such versatility to repair and regenerate various tissue types, therapies using ASC has offered a paradigm shift that may provide an alternative solution to numerous diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They release important cytokines such as epidermal growth factor (EGF), transforming growth factor beta (TGFB), vascular endothelial growth factor (VEGF), as well as other cytokines and new cartilage proteins that are essential in combating OA and degenerative processes. It has also been suggested that stem cells could release cytokines and proteins that could help combat neurogenic pain, which would have numerous benefits in treating OA pain [40,42]. Further research needs to be done in order to better understand stem cells mechanism of action in regard to their immunomodulatory, differentiating, paracrine, regenerative, and anti-inflammatory abilities as well as their cellular trafficking mechanisms.…”
Section: Referencesmentioning
confidence: 99%